Re-enacting the Trauma of Cultural Shame in Merle Hodge’s Crick Crack, Monkey - مجدة عطية; إنجي حلوم (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This article demonstrates how Merle Hodge’s Crick Crack, Monkey projects an awareness of traumatic shame in the Caribbean transnational travel setting and contributes to the understanding of the epistemology of cultural shame. Hodge’s narrative introduces disruptive trauma to experiment with the possibilities of transcending it in a way that evokes Dominique LaCapra’s theory regarding the two forms of remembering trauma: "acting out" and "working through." In this context, Hodge’s Crick Crack, Monkey also reads Homi Bhabha’s two notions of mimicry and stereotype to propose a healing strategy unrecognized by the traumatized protagonist. Reading the reenactment of cultural trauma of shame in Hodge’s narrative introduces a genre of resistance and transformation through the investigation of the possible ways of working through trauma.